2019
DOI: 10.32479/ijefi.8583
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Earnings Management and Capital Structure: An Empirical Study on Jordanian Firms Listed in Amman Stock Exchange

Abstract: The purpose of this study is to investigate the association between earnings management, measured by the absolute unexpected accruals and the firm's capital structure. The study sample consists of 44 manufacturing Jordanian firms listed in the Amman Stock Exchange during the 5 years (2008)(2009)(2010)(2011)(2012), a total of 220 (firm-year) observations. The study provides evidence supporting the hypothesized association between capital structure and the absolute unexpected accruals. Consistent with most prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The study population consists of all the Jordanian industrial shareholding companies registered in the Amman Stock Exchange which count (54) company (Al-Mohareb & Alkhalaileh, 2019). The researchers adopted a sample random technique because of the large population.…”
Section: Methodsmentioning
confidence: 99%
“…The study population consists of all the Jordanian industrial shareholding companies registered in the Amman Stock Exchange which count (54) company (Al-Mohareb & Alkhalaileh, 2019). The researchers adopted a sample random technique because of the large population.…”
Section: Methodsmentioning
confidence: 99%
“…debt. An early study by Al-Mohareb & Alkhalaileh (2019) reported an average leverage of 30% for Jordanian firms.…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Numerous studies tried to link earnings management to a different set of explanatory variables, they have shown wide set of variables for earnings management determinants, incentives and constraints, such as firm performance, dividends policy, surplus free cash flow, ownership structure, managerial ownership, board of director's characteristics, audit committee characteristics, corporate governance mechanisms, Chief Executive Officer role duality, investor protection, voluntary disclosure, among others (see for example, Jensen, 1993;Yermack, 1996;Peasnell et al, 2000;Klein, 2000;Xie et al, 2003;Bedard et al, 2004;Abbott et al, 2004;Yang & Krishnan, 2005;Lin et al, 2006;Naveen et al, 2007;Lin & Hwang, 2010;Al-Fayoumi et al, 2010;Ghosh et al, 2010;Azzoz & Khamees, 2016;Abbadi et al, 2016;Al-Mohareb &Alkhalaileh, 2019 andDayak &Al-Mughrabi, 2020). As a result of the global financial crisis, the interest of studying earnings management has been increased lately.…”
Section: Related Literaturementioning
confidence: 99%